Divergent Palladium‐Catalyzed Cross‐Coupling of Nitropyrazoles with Terminal Alkynes. Issue 20 (6th May 2018) - Ha, Hyeri; Shin, Changhoon; Bae, Seri; Joo, Jung Min
Abstract : Facile homo‐coupling of terminal alkynes, which generates conjugated diynes, is an undesired pathway in the development of transition‐metal‐catalyzed oxidative C–H functionalization of (hetero)arenes with terminal alkynes. By incorporating this process into a catalytic cycle, we achieved regio‐ and stereoselective hydroarylation of nitropyrazoles with the resulting 1, 3‐diynes. A simple change in the stoichiometry and oxidant allowed direct C–H alkynylation of nitropyrazoles, producing the corresponding alkynyl pyrazoles. Abstract : Homo‐coupling of terminal alkynes, which provides conjugated diynes, was incorporated into a sequential process to couple with nitropyrazoles with high regio‐ and stereoselectivity. In addition, direct C–H alkynylation was achieved by carefully controlling the stoichiometry of the catalysts, alkynes, and oxidants.